2011
DOI: 10.1177/1742395311417639
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities in women with Celiac Disease

Abstract: Despite largely adhering to a gluten-free diet, a substantial subset of women with Celiac Disease report clinically relevant symptoms of depression and disordered eating; such symptoms are associated with increased psychosocial distress in other domains. These results suggest potential to improve the patient well-being through attention to psychosocial care, in addition to existing dietary recommendations for individuals with Celiac Disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 35 publications
(40 reference statements)
2
109
0
5
Order By: Relevance
“…When reported, the mean scores for GFD adherence indicated that, on average, participants were highly adherent (Arigo et al, 2012;Edwards-George et al, 2009;Mahadev et al, 2015;Sainsbury et al, 2013aSainsbury et al, , 2013b. The proportion of each sample falling into the inadequate adherence range (21.4-43.4%) suggested lower rates of strict adherence though Mahadev et al, 2015;Nachman et al, 2009;Nachman et al, 2010;Sainsbury et al, 2013aSainsbury et al, , 2013b).…”
Section: Gfd Adherence and Depressive Symptomsmentioning
confidence: 98%
See 4 more Smart Citations
“…When reported, the mean scores for GFD adherence indicated that, on average, participants were highly adherent (Arigo et al, 2012;Edwards-George et al, 2009;Mahadev et al, 2015;Sainsbury et al, 2013aSainsbury et al, , 2013b. The proportion of each sample falling into the inadequate adherence range (21.4-43.4%) suggested lower rates of strict adherence though Mahadev et al, 2015;Nachman et al, 2009;Nachman et al, 2010;Sainsbury et al, 2013aSainsbury et al, , 2013b).…”
Section: Gfd Adherence and Depressive Symptomsmentioning
confidence: 98%
“…Following title and abstract screening, 84 papers were retained for full-text screening, which resulted in 8 studies (reported in 9 papers) being included in the meta-analysis (Arigo, Anskis, & Smyth, 2012;Edwards-George et al, 2009;Kerswell & Strodl, 2015;Mahadev, Gardner, Lewis, Lebwohl, & Green, 2015;Nachman et al, 2009;Nachman et al, 2010;Sainsbury, Mullan, & Sharpe, 2013a, 2013bWeiss et al, 2013). All 8 studies measured depressive symptoms; no studies that measured clinically diagnosable depression and met other criteria were identified.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations